Defences to copyright infringement : creativity, innovation and freedom on the internet - Karapapa, Stavroula (Oxford University Press, 2020)
This volume analyses how available copyright defences accommodate modern uses of copyright works, and how EU copyright defences might be framed to promote creativity, technological innovation, and the development of new services and business models on the internet.